166k views
2 votes
Transform the given quadratic function into vertex form f(x) = quadratic function into vertex form f(x) = quadratic function into vertex form
f(x) = (x-h)^(2) + k by completing the square.
a(x-h)^(2) +k by completing the square.


f(x) = 3x^(2) -4x-6

User Romero
by
5.5k points

1 Answer

5 votes

Answer:


f(x) = 3(x -(2)/(3))^2 -(22)/(3)

The vertex is
((2)/(3), -(22)/(3))

Explanation:

For a general quadratic function the form is:


ax ^ 2 + bx + c

For the function


f(x) = 3x ^ 2 -4x -6

Take common factor 3.


f(x) = 3(x ^ 2 -(4)/(3)x - 2)

The values of the coefficients for the function within the parenthesis are the following:
a = 1,
b = -(4)/(3),
c = -2

Take the value of b and divide it by 2. Then, the result obtained squares it.


(b)/(2)= -(2)/(3)


((b)/(2))^2=(4)/(9)

Add and subtract
(4)/(9)


f(x) = 3([x ^ 2 -(4)/(3)x +(4)/(9)]- 2-(4)/(9))

Write the expression of the form


f(x) = (x-(b)/(2))^2 +k


f(x) = 3(x -(2)/(3))^2 -(22)/(3)

The vertex is
((2)/(3), -(22)/(3))

User Kurt Pfeifle
by
5.9k points